Electronic nicotine delivery system (ENDS) battery-related burns presenting to US emergency departments, 2016 - Catherine G. Corey; Joanne T. Chang; Brian L. Rostron (BMC, 2018)
Abstract Background Currently, an estimated 7.9 million US adults use electronic nicotine delivery systems (ENDS). Although published reports have identified fires and explosions related to use of ENDS since 2009, these reports do not provide national estimates of burn injuries associated with ENDS batteries in the US. Findings We analyzed nationally representative data provided in the National Electronic Injury Surveillance System (NEISS) to estimate the number of US emergency department (ED) visits for burn injuries associated with ENDS batteries. We reviewed the case narrative field to gain additional insights into the circumstances of the burn injury. In 2016, 26 ENDS battery-related burn cases were captured by NEISS, which translates to a national estimate of 1007 (95%CI: 357-1657) injuries presenting in US EDs. Most of the burns were thermal burns (80.4%) and occurred to the upper leg/lower trunk (77.3%). Examination of the case narrative field indicated that at least 20 of the burn injuries occurred while ENDS batteries were in the user's pocket. Conclusions Our study provides valuable information for understanding the current burden of ENDS battery-related burn injuries treated in US EDs. The nature and circumstances of the injuries suggest these incidents were unintentional and would potentially be prevented through battery design requirements, battery testing standards and public education related to ENDS battery safety.